Analysis of road traffic safety in Minna Niger State, Nigeria - Oyetubo, Adebayo Owolabi (Logistics and sustainable transport, 2018)
Road traffic accident is one of the major causes of death in Nigeria. Road accidents have taken away so many lives in Nigeria today that hardly does any single disease match its mortality prowess. People have died prematurely and properties worth several millions of Naira have been lost as a result of road traffic accident. This paper gives a full discussion on road traffic safety issues and the methodology used were through the collection of data using questionnaire and accident information from the Nigeria Police Force, FRSC etc. The primary information for this research was sourced through the use of structured questionnaire, personal observation and interviews of road users in the study area. Secondary data emanated from published and unpublished sources such as government records, internet, journals, books etc. The findings were presented in descriptive and inferential form using frequencies, percentages, tables, mean and chi-square analytical techniques. The findings from the study revealed among many others; that Male involved more in road accident compare to female counterpart in Minna Niger State. Private car had more accident compare to Taxi, The number of accident in each zone does not depend on the population of that zone, etc.
Keywords: accident; fatalities; nesreče; promet; safety; smrtne žrtve; traffic; varnost; vehicle; vozila